Medico-legal Assessment of Non-fatal Cases of Fall from Height in Karachi - Syed Perwez Alam; Roohi Ehsan; Wasiq Ahmed; Fahad Hussain Mirza (ziauddin University, 2024)
Background: Fall from height is a tragedy, largely avertable, often leading to death or morbidity. Apart from the physical dimension, it also has important medico-legal implications. There is a dearth of serious study to document the overall fall from height cases in the metropolis of Karachi or to formulate suggestions to improve the situation. The current study has been undertaken in this direction. Objective: To assess and document the incidence of medico-legally relevant cases of fall from height in the metropolis of Karachi and to suggest ways to minimize this mishap. Methods: Descriptive, retrospective, cross-sectional study of medico-legally relevant cases of falls from height in Karachi registered from 1st January, 2007 to 31st December, 2011; the data having been retrieved from the three medico-legal sections of Karachi located at Abbasi Shaheed Hospital, Jinnah Post-graduate Medical Centre & Civil Hospital and from the Police Surgeon's Office, Karachi. Findings were expressed in numbers & percentages. Results: The total number of registered medico-legal cases of fall from height in Karachi during the study period was 1029. Of these 49.17% (n=506) were reported at ASH, followed by 28.67% (n=295) at CHK and 22.16% (n=228) at JPMC. Of the total number of fall cases, 86.01% (n=885) were non-fatal and 13.99 (n=144) proved fatal. Further, 51.41% (n=455) of the non-fatal cases were referred to ASH while 28.59% (n=253) went to CHK and 20% (n=177) to JPMC. Most of the referrals to ASH were due to location of the hospital. Conclusion: Fall from height is one of the leading causes of medico-legal cases in Karachi with a high morbidity rate as well as mortality with about 15% of them being fatal in the five year period 2007-2011. Despite the incidence, most of these mishaps are preventable. As majority of these cases involve the construction industry, a multi-pronged team effort is required to improve the situation. Key Words: Falls from Height, Karachi, Medico-legal, Morbidity, Abbasi Shaheed Hospital.